Photodegradation of Indigosol Blue Dye Using TiO2/Natural Zeolite Photocatalyst - Lulu’atul Hamidatu Ulya; Husnul Fatimah; Nasrul Alif (Jurnal Kimia Valensi, 2022)
Indigosol blue is one of the dyes that has not been widely studied for photodegradation. This study aims to determine the photodegradation activity of indigosol blue using TiO2/Natural zeolite. TiO2 embedded in natural zeolite was synthesized using the sol-gel method. The synthesis results were characterized using X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF), and UV-Vis Diffuse Reflectance Spectroscopy (DRS). The characterization of TiO2-zeolite obtained a bandgap energy of 2.62 eV that could be seen in the UV-Vis DRS spectra. UV light is used during the photodegradation process to irradiate TiO2-zeolite photocatalyst. The results show that the optimum mass of natural TiO2-zeolite photocatalyst was 0.02 g with a degradation percentage of 58.3%. The optimum radiation time was 30 min with a degradation percentage of 58.7%, and the optimum concentration of blue indigosol was 600 ppm with a degradation percentage of 58.7%. TiO2/Natural zeolite photocatalyst could degrade indigosol blue dye effectively at the optimum condition.